Urban planning : a conceptual framework - Ngah, Ibrahim (Fakulti Alam Bina, UTM, 1998)
This paper examines the concept and approaches in urban planning. Urban planning is conceived as physical planning dealing with three key systems i.e. activity systems, land development system and environmental system. There has been shifting in emphasis in the practice of urban planning from a purely urban design approach to emphasis on environmental issues, planning methods and development of IT. This paper also touches on the importance ofpartners hip approach in plan making and implementation.